2016
DOI: 10.1016/j.neulet.2015.12.032
|View full text |Cite
|
Sign up to set email alerts
|

Tempol protects sleep-deprivation induced behavioral deficits in aggressive male Long–Evans rats

Abstract: Earlier, we reported that elevated anxiety-like behavior and high aggression in aged retired breeder Long-Evans (L-E) rats was associated with increased plasma corticosterone and elevated oxidative stress levels. In the present study, we examined how this aged aggressive and anxious rat strain responds to acute sleep deprivation (24 h) and whether their behaviors can be modulated via antioxidant tempol treatment. Four groups of L-E rats were utilized: naïve control (NC), tempol treated control (T+NC), sleep de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 33 publications
1
6
1
Order By: Relevance
“…However, another study also comparing the effects of the single and multiple platforms methods, applied during 4 days, on the HPA axis activity of male rats showed that both protocols caused an increased secretion of corticosterone and ACTH, and confirmed that this effect was stronger in the single platform paradigm [138]. The stressful aspect of the multiple platforms apparatus was further highlighted in several other studies showing that 18 h to 21 days of REM-sleep suppression induced an increase in corticosterone and/or ACTH in male rats [139][140][141][142][143][144][145][146][147][148] and mice [149,150]. Other related methods using two small platforms or a 'grid over water' have been shown to also induce an increase in corticosterone in male mice after 2 and 3 days, respectively, [151,152].…”
Section: Do Sleep-deprivation Procedures In Rodentssupporting
confidence: 57%
See 1 more Smart Citation
“…However, another study also comparing the effects of the single and multiple platforms methods, applied during 4 days, on the HPA axis activity of male rats showed that both protocols caused an increased secretion of corticosterone and ACTH, and confirmed that this effect was stronger in the single platform paradigm [138]. The stressful aspect of the multiple platforms apparatus was further highlighted in several other studies showing that 18 h to 21 days of REM-sleep suppression induced an increase in corticosterone and/or ACTH in male rats [139][140][141][142][143][144][145][146][147][148] and mice [149,150]. Other related methods using two small platforms or a 'grid over water' have been shown to also induce an increase in corticosterone in male mice after 2 and 3 days, respectively, [151,152].…”
Section: Do Sleep-deprivation Procedures In Rodentssupporting
confidence: 57%
“…Moreover, studies reported that pharmacological inhibition of corticosterone synthesis during REM-sleep deprivation in male rats resulted in impairment of sleep rebound [135], suggesting that the activation of the HPA axis following REM-sleep suppression is necessary for proper sleep recovery. The link between REM sleep and stress-associated behaviour has been further highlighted by studies reporting that, in addition to the increased corticosterone level, specific REMsleep deprivation induces higher anxiety and depressive-like behaviour in rats [145,146,153,154,165]. All these findings underline the crucial effects of sleep loss, and in particular the suppression of REM sleep, on physiological and behavioural stress coping mechanisms.…”
Section: What Are the Stress-associated Consequences Of Sleep Deprivation In Rodents?mentioning
confidence: 94%
“…Studies have shown that SD leads to poor mood ( 5 ) and increases nerve sensitivity to negative emotional stimuli ( 6 ). For example, extending waking time induces irritability, aggressiveness, and increased anxiety ( 7 ). Furthermore, reduced control over emotional states can lead to more harmful actions ( 8 ).…”
Section: Introductionmentioning
confidence: 99%
“…Sleep deprivation is related to several adverse physiological consequences such as disturbances of metabolic, immune, and endocrine function [9] with harmful stress that negatively affects the physiology of vital organs as the liver, kidneys, brain, and reproductive organs [10]. As a consequence of sleep deprivation is an increase in the level of stress factors that accelerates biological aging [11] and decreases serum testosterone concentration [12]. In healthy men, sleep deprivation has recorded a reduction in serum androgens including testosterone [10], which can hinder gonads function and greatly decline the fertility rate [13].…”
Section: Introductionmentioning
confidence: 99%